HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN AKURASI SERVIS BAWAH BOLAVOLI PADA SISWA PUTERA KELAS V SDN 002 PASAR BENAI KABUPATEN KUANTAN SINGINGI - Werdalis Werdalis; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, Based on observations while the researchers did in class V SDN 002 Pasar Benai Regency Kuantan Singingi, especially in the lower servicing ability is not good enough, the service under which do tend to be less focused on the target field plots, and also often do not pass through the net. Researchers suspect the problem is due to the strength of the arm muscles students so the purpose of this study was to determine the relationship of the arm and shoulder muscle strength with accuracy under volleyball serve. This type of research is correlational study sample 22 students of class V SDN 002 Pasar Benai with total sampling technique. Data obtained from the test results for the body lift arm and shoulder muscle strength and accuracy tests under volleyball serve. Data analysis using product moment correlation and Liliefors test for normality. Based on the analysis of data obtained rhitung = 0518> rtabel = 0433 then it can be concluded as follows: There is a significant relationship muscle strength of the arms and shoulders with accuracy down on the service. Men's Class V students of SDN 002 Pasar Benai Singingi Kuantan District.Keywords : Arms and Shoulders, Strength Muscle, Under Service, Voleyball